Lean Service Analysis to Identify And Minimize Waste in PT XYZ Non-Production and Investment Procurement Process using Value Stream Mapping - Putri, Arif Faniya; Hasan Bisri (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
The non-production and investment procurement process plays a crucial role in supporting the smooth operation of a company. However, this process often faces problems in the form of waste that causes lengthy processing times. This study aims to identify the dominant types of waste and develop proposals for improving the non-production and investment procurement process at PT XYZ using a lean service approach. The methods used include Value Stream Mapping to map the current process conditions, a questionnaire to determine critical waste, a Fishbone Diagram to analyze the root causes of waste, and the 5S method to formulate improvement proposals. The results show that the dominant critical wastes in the procurement process are waiting, transportation, and inappropriate processing. The Process Cycle Efficiency (PCE) value in the current state is 39.0% and increases to 49.39% in the proposed state (future state), indicating potential for increasing process efficiency. The formulated improvement proposals are expected to minimize waste and increase the effectiveness of the non-production and investment procurement process at PT XYZ.